Patents: A Means to Innovation or Strategic Ends? - Jiri Schwarz; Martin Stepanek (Charles University in Prague, Institute of Economic Studies (IES), 2016)
This paper utilizes a data set of over 208,000 U.S. patents applied for between 1975 and 2010 to study development of strategic patenting over time and across industries. With received citations as a measure of patent social value, we use data envelopment analysis to estimate firm-level relative importance of strategic versus protective patenting. Our novel identification strategy reveals there was an almost universal drop in patent social value in the second half of the 1990s, signaling a shift towards the strategic use of patents. But the development of patenting strategies continued even after 2000 with semiconductor companies increasing their focus on patent value relative to companies from other industries. On average, aerospace and software companies preferred the production of valuable patents, but patenting strategies can differ vastly even among companies operating within one industry. The results confirm our expectations regarding the focus of aerospace companies on socially valuable patents.
Keywords: D23; K11; O32; O34; 330; patents; patent value; strategic patenting; intellectual property rights